2008
DOI: 10.1590/s0100-83582008000300003
|View full text |Cite
|
Sign up to set email alerts
|

Análise morfológica de Sagittaria montevidensis desenvolvida em diferentes condições de inundação

Abstract: RESUMO -O cultivo de arroz irrigado em sistema pré-germinado tem permitido o desenvolvimento de plantas daninhas aquáticas, como as da espécie Sagittaria montevidensis (sagitária), a qual desenvolveu biótipos resistentes a herbicidas inibidores de ALS, no Estado de Santa Catarina. No presente trabalho, objetivou-se examinar as respostas morfológicas de sagitária quanto à variação da lâmina d'água, crescendo sob condições ambientais controladas. Os tratamentos foram representados pelas seguintes condições de in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Regarding aquatic species, Sagittaria montevidensis stands out because it is a rhizomatous species which adapts to the ecological amplitude. When it is not controlled, a broad amount of seeds can develop on the soil and contribute to increase the population in the next season (CASSOL et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding aquatic species, Sagittaria montevidensis stands out because it is a rhizomatous species which adapts to the ecological amplitude. When it is not controlled, a broad amount of seeds can develop on the soil and contribute to increase the population in the next season (CASSOL et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…This may be related to the absence of histological differentiation of plant tissues under different water levels. Cassol et al (2008) showed that increases in water levels did not lead to the synthesis of secondary cell walls. In our study, however, plants were submitted to a strong water flow during flood periods, which may have caused the investment in greater basal areas, petiole diameter and petiole biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Structures such as leaves and petioles can suffer changes in number, length, biomass and diameter in response to environmental variations, such as water level fluctuations (Cassol et al, 2008). Major key life-history traits that suffer morphological changes enhancing the survival of such plants include: tissues elongation, new leaves recruitment, petioles and basal plant diameters, and emergent surface area (Cooling et al, 2001;Deegan et al, 2007;Iwanaga and Yamamoto, 2008;Xie et al, 2008;Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grande do Sul (RS), where the system of pregerminated seeding is used (CASSOL et al, 2008). Chemical control has been widely used in SC for the control of S. montevidensis, with at least one herbicide application during the rice crop season.…”
Section: A Sagitária Tem Sido Considerada Uma Das Principais Plantas mentioning
confidence: 99%